THE CONCEPT OF THE SYMBOL AND THE LINGUOCULTUROLOGICAL APPROACH - Khusanova Mashkhura Akhmadjonovna (Bright Mind Publishing, 2025)
This article analyzes the artistic symbols found in the works of Shukur Kholmirzayev, a prominent representative of Uzbek literature, focusing on their linguocultural content and their role in expressing the national cultural code. Natural elements, colors, objects, and figurative expressions employed in the writer’s works are interpreted in close connection with the national worldview, folk traditions, and cultural values. The study considers symbols not only as artistic and aesthetic devices, but also as linguocultural units that reflect the Uzbek mentality, way of life, and spiritual values.
Keywords: Symbol, sign, linguoculturology, artistic image, national culture, semantics, connotation, concept, cultural code.